Evaluation of the characteristics of various types of finishing coils for the embolization of intracranial aneurysms in an experimental model with radiolucent coils. Issue 2 (April 2017) - Ota, Keisuke; Matsubara, Noriaki; Miyachi, Shigeru; Izumi, Takashi; Ito, Masashi; Asai, Takumi; Yamanouchi, Takashi; Wakabayashi, Toshihiko
In endovascular coil embolization of intracranial aneurysms, very soft coils, often called "finishing coils, " are usually selected in the final stage of coil embolization. The authors developed a radiolucent coil made of thin nylon thread to evaluate the performance of coils under a situation simulating the course of embolization. The characteristics of various types of finishing coils were investigated using radiolucent coils. Experimental embolization was performed with a silicone aneurysm filled with radiolucent coils simulating the final stage of embolization. Three indices, i.e. area, perimeter, and circularity of the inserted coils, were investigated on the X-ray images after coil insertion. The coils used were as follows: Target Ultra Helical, MicroPlex Hypersoft, Axium Helix, ED Coil Extrasoft, and DeltaPlush. In the analysis of area and perimeter, there were significant differences in multiple comparisons. There was no significant difference in circularity, although it was generally ranked in order by coil brand. Target Ultra and MicroPlex Hypersoft had higher scores for area and perimeter and lower scores for circularity, in contrast to DeltaPlush, which had lower scores for area and perimeter and a higher score for circularity. Based on these results, the finishing coils were divided into three groups: Target Ultra Helical and MicroPlex Hypersoft; Axium Helix and ED Coil Extrasoft; DeltaPlush. They are better for use in early, midst, and end of finishing, respectively. The characteristics of various finishing coils were evaluated, and the results obtained reflected actual clinical experience and provide useful information to appropriately select finishing coils.